Acute performance decrement following training based on the phases of the 200-meter races in Paralympic canoe sprint kayak athletes - Neto, F. R.; dos Santos, L. G. T. F.; de Campos, L. F. C. C.; Costa, R. R. G.; Winckler, C. (Perceptual and Motor Skills, 2025)
Background: Tailored training methods for 200-m races may improve in Paralympic canoe sprint (PCS) kayaking. Understanding methods impact on fatigue can help coaches and athletes in guiding training periodization. Purpose: The aim of this study was to assess the acute performance decrement (APD) in PCS athletes after phase-specific training sessions for the 200-m kayak race, and compare the training loads of three different methods and their correlation with APD.